Intellectuals and the State in Iran: Politics, Discourse, and the Dilemma of Authenticity by Negin Nabavi (Gainesville: University of Florida Press, 2003. 221 pages.) (American Journal of Islam and Society, 2004)
Negin Nabavi’s Intellectuals and the State in Iran comes at a time when aprocess of soul-searching by some Iranian intellectuals that started immediately after the triumph of Islamic revolution has now faded away, withoutyielding any satisfactory results. This process was inspired by the question:What role did the (secular left-leaning) intellectuals play in the revolution’striumph, which culminated in an Islamic state inherently opposed to theactivities of these same intellectuals? This important topic, of course, givesrise to the familiar question of “What is meant by an intellectual?” whichNabavi addresses in the book’s first part. Having given a historical perspectiveon the development and evolution of intellectualism in Iran, she concludesthat a distinguishing character of the Iranian intellectual was “theintellectual’s task to take a stance and engage with issues in society” (p. 3);where “dissent” was “a necessary component in the career of any Iranianintellectual” (p. 18).In part two, Nabavi discusses the processes that led to the “radicalizationof the Iranian intellectual.” Here she explores the emergence of what shecalls “the Third-Worldist intellectual” and the cooptation of a great numberof intellectuals by the Pahlavi regime . According to her, during this period(1963-70) “the notions of the ‘native’ and the ‘authentic’ became so pervasivethat even the establishment could not remain impervious to them” (p.106). The epilogue briefly touches upon the relationships between intellectualsand the revolution, where the author concludes that the intellectuals“lost out in the year that followed the revolution” (p. 149) ...